Supply chain uncertainty and environmental management - Stephan Vachon; Sara Hajmohammad (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2016)
This manuscript examines the impact of supply chain uncertainty on environmental management spending in manufacturing plants. Building on the attention-based view of the firm (ABV), the basic premise is that with increased uncertainty in the supply chain, managers' attention to environmental management lessens which in turn leads to (i) fewer resources devoted to green issues within the plant and (ii) a bias to use resources toward less disruptive pollution control approaches rather than pollution prevention approaches. Data from a survey of 251 Canadian manufacturing plants was used to test the link between the level of uncertainty in the supply chain and environmental management decisions. The results indicate that supply chain uncertainty does not have a substantial impact on the level of environmental spending in a plant but has a substantial and significant impact on the allocation of the spending between pollution prevention and pollution control. More particularly, as supply chain uncertainty increases, organizations shift their resources away from pollution prevention to favor pollution control approaches.
Keywords: 650; Supply chain management; Environmental management